Assessment of Bacillus subtilis applied in rice-crayfish coculture system on physicochemical properties, microbial sulfur cycling, Cd accumulation and bioavailability. (25th December 2022) - Mo, Aijie; Li, Hong; Zhai, Yuxiang; Yang, Huijun; Wang, Jianghua; Wang, Yuesong; Yi, Linyuan; Guo, Wei; Yuan, Yongchao
Abstract: Bacillus subtilis is frequently used commercially in rice-crayfish coculture system (RCCS) to modify the physicochemical characteristics of soil and water. However, given the intensification of cadmium (Cd) contamination in RCCS and potential implications for food safety, the impacts of this modulation on the Cd bioavailability and accumulation need to be more thoroughly assessed. Here, B. subtilis was inoculated into RCCS containing different levels of soil Cd through an outdoor mesocosm experiment. Results showed that the abundance of B. subtilis in the soil was highest on the 1st day after inoculation and appeared the second peak on the 2nd week. 40–128-fold increase in B. subtilis abundance in crayfish intestines was found in the B. subtilis added groups compared to the non- B. subtilis added groups. Additionally, the Cd accumulation in crayfish and rice tissues rose significantly when the soil Cd content raised. However, with the improvement of soil pH, oxidation-reduction potential (ORP), nitrification potential (NP), acid volatile sulfide (AVS) and sulfur reducing bacteria abundance, and the decrease of organic matter (OM) at 2 W and 8 W, the addition of B. subtilis into RCCS with various Cd contents significantly reduced the Cd accumulation and the soil Cd bioavailability. The low bioavailability of Cd was characterized by the reduction of exchangeable Cd (EXC-Cd) and the grows of Fe–Mn oxides bound Cd (FeMnOx-Cd) and residual Cd (RES-Cd). Specifically, the soil EXC-Cd was negatively correlated with soil pH (−0.647), OPR (−0.663) and NP (−0.811). In short, the obtained results demonstrated that B. subtilis was able to stabilize the physicochemical properties of soil and water in RCCS, while mineralizing Cd and attenuating Cd accumulation in the crayfish and rice, suggesting that B. subtilis can be used as a cleaning probiotic applied in rice and aquatic animals coculture system. Graphical abstract: Image 1 Highlights: Application of B. subtilis mitigated RCCS Cd accumulation in Cd-polluted soil. The stable colonization of B. subtilis in crayfish gut might limit Cd absorption. B. subtilis inhibited soil Cd bioactivity by improving physicochemical properties. The supply of B. subtilis also played a vital part in Cd mineralization.